6g+20g=2g+36

Simple and best practice solution for 6g+20g=2g+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g+20g=2g+36 equation:


Simplifying
6g + 20g = 2g + 36

Combine like terms: 6g + 20g = 26g
26g = 2g + 36

Reorder the terms:
26g = 36 + 2g

Solving
26g = 36 + 2g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-2g' to each side of the equation.
26g + -2g = 36 + 2g + -2g

Combine like terms: 26g + -2g = 24g
24g = 36 + 2g + -2g

Combine like terms: 2g + -2g = 0
24g = 36 + 0
24g = 36

Divide each side by '24'.
g = 1.5

Simplifying
g = 1.5

See similar equations:

| 4y^2-8=7y | | 8y^2=12y | | 6(1+4n)=-162 | | 5s-9+7s=88 | | -130=-10n | | 7(5x-4)=35x-28 | | 12n+483=21n+462 | | 12n=54+12 | | 2y+3x=180 | | 16yx^2+16y^3+49y=0 | | 10z^2=-53x+399 | | 0.18(y-4)+0.04y=0.14y-1.5 | | .5x-8=x-2 | | 2(b+1)-(6+b)=-6 | | x(120-2x)=1512 | | (x+15)+(2x-18)=180 | | 9g+15=96 | | 15n=54+12 | | -200=20x | | z^2=-3z+3 | | 2x-7x=30 | | 8(x-2)=4(x+3) | | 49x-16x^3-16xy^3=0 | | sin^2x-9cosx-9=0 | | 1.2X-0.8=16 | | 12x^2-102x-180=0 | | 45x^2+18x-5=0 | | 3x-6x+4=32 | | 7(150)+12x=1986 | | 4x-7=7x-13 | | 8y^2=20y | | 0=x^3-13x^2-14x |

Equations solver categories